Dialectal elements in the phraseology of the Russian dialect of Old Believers from the Suwałki-Augustów region - Grupa-Dolińska, Magdalena (Papers in Linguistics, 2022)
The aim of the article is to present dialectal elements preserved in the phraseological stock of the Russian dialect of the Old Believers living in the Suwałki-Augustów region. The Old Believers arrived in the Polish territories about two centuries ago. Upon arrival they used the Russian dialect which belonged to the Novgorod-Pskov type (western type of Central Russian dialect). Many dialectal elements such as specific lexemes and morphological features have survived in their traditional dialect since then, despite increasing influence of the Polish language. The current study focuses on the phraseological stock of the dialect because within the structure of phraseological units there are not only contemporary words but also archaic components. Thus, it is a valuable source of knowledge about linguistic features of the language in question.